High-density freestanding graphene/carbide-derived carbon film electrodes for electrochemical capacitors. (July 2017) - Alhabeb, Mohamed; Beidaghi, Majid; Van Aken, Katherine L.; Dyatkin, Boris; Gogotsi, Yury
Abstract: Freestanding films of reduced graphene oxide (rGO) have attracted much attention as electrodes for electrochemical capacitors, especially for flexible device applications. Here, for the first time, we report binder-free supercapacitor electrodes made of highly porous carbide-derived carbon (CDC) nanoparticles as spacers between thermally reduced graphene oxide (rGO) sheets. The addition of CDC between the rGO layers increases the wettability and accessibility of active material to the electrolyte ions, which improves electrochemical performance. The resulting electrodes exhibit high capacitance of over 210 F/g, high power densities at 100 mV/s and 10 A/g charge/discharge rates, and long stability of over 10, 000 cycles in an aqueous electrolyte. Moreover, hybrid rGO/CDC electrodes, in contrast to solely rGO-based counterparts, maintained high gravimetric capacitance as the electrode thickness increased from 5 μm to ∼50 μm. This hybrid electrode material design is greatly viable in high-power energy storage devices. Graphical abstract: